Komposisi Jenis dan Struktur Vegetasi Tepi Hutan, Taman Nasional Gunung Ciremai, Jawa Barat: Floristic Composition and Vegetation Structure in The Edge Forest, Mount Ciremai National Park, West Java - Iskandar, Suci Dian Hayati; Dwika Bramasta; Peniwidiyanti; Nilna Kamala; Muhammad Basrowi; Sulistijorini (Departemen Biologi, Institut Pertanian Bogor, 2021)
Mount Ciremai National Park has a high ecological function as a major catchment and water source areas. The objective of this research was to obtain information on floristic composition and structure in the edge forest of Seda Block, Mount Ciremai National Park. To carried out the research, the method used in the analysis vegetation was quadrat transect at an elevation of 602-614 m asl. The results showed that species composition dominated by the families of Euphorbiaceae and Moraceae, consisting of 3 stratas of heading A to C where strata A occupied by Elaeocarpus sp. (40 m) and Ficus involucrata (30 m). Ficus involucrata has the widest heading cover on the observation plot. The condition of the forest quantitative structure generally demonstrates good conditions by forming a reversed J curve, as well as a relatively moderate diversity of plant species and there are no species of plant that dominate the forest edges.